Increased ice flow in Western Palmer Land linked to ocean melting - Stephen Cornford (Geophysical Research Letters, 2017)
Satellite observations of West Palmer Land show that the majority of the glaciers flowing into the the George VI ice shelf sped up between 1995 and 2015. The data themselves do not have complete coverage for any given year, but we address this by using them to calibrate a high-resolution ice flow model. As a result we can quantify the speed-up and conclude that discharge has increased from to 88 to 100 cubic kilometres per year, and that the pattern of change is consistent with a dynamic response to ocean driven ice shelf thinning.